2022
DOI: 10.1161/circulationaha.122.059994
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age on the Diagnosis of Myocardial Infarction

Abstract: Background: The 99th centile of cardiac troponin, derived from a healthy reference population, is recommended as the diagnostic threshold for myocardial infarction, but troponin concentrations are strongly influenced by age. Our aim was to assess the diagnostic performance of cardiac troponin in older patients presenting with suspected myocardial infarction. Methods: In a secondary analysis of a multicenter trial of consecutive patients with suspected m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…We read with great interest the study of “Influence of Age on the Diagnosis of Myocardial Infarction” by Lowry et al 1 The authors found that cardiac troponin concentrations above the recommended sex-specific 99th percentile are common in older patients, affecting nearly half of those >90 years of age, and no approach achieved parity in the diagnosis between older and younger patients with specificity and positive predictive value (PPV) reducing with advancing age, regardless of the threshold adopted.…”
Section: To the Editormentioning
confidence: 99%
“…We read with great interest the study of “Influence of Age on the Diagnosis of Myocardial Infarction” by Lowry et al 1 The authors found that cardiac troponin concentrations above the recommended sex-specific 99th percentile are common in older patients, affecting nearly half of those >90 years of age, and no approach achieved parity in the diagnosis between older and younger patients with specificity and positive predictive value (PPV) reducing with advancing age, regardless of the threshold adopted.…”
Section: To the Editormentioning
confidence: 99%
“…We commend Lowry et al on their recent retrospective analysis of age-adjusted, sex-specific 99th percentile upper reference limits for high-sensitivity (hs) troponin-I in the High-STEACS (High-Sensitivity Troponin in the Evaluation of Patients With Acute Coronary Syndrome) trial. 1,2 The authors found that, compared with currently recommended sex-specific 99th percentile upper reference limits, the use of age-adjusted, sex-specific 99th percentile upper reference limits improved specificity (91.3% versus 82.6%) and positive predictive value (59.3% versus 51.5%) for myocardial infarction (MI) diagnosis in older adults. However, these improvements come at the cost of a significant reduction in sensitivity.…”
Section: Letter To the Editormentioning
confidence: 99%
“…We wish to thank Chen et al and Gibson et al for their thoughtful appraisal of our recent article, in which we evaluated the impact of age on the diagnostic performance of high-sensitivity cardiac troponin for myocardial infarction. 1…”
Section: In Responsementioning
confidence: 99%
“…
We wish to thank Chen et al and Gibson et al for their thoughtful appraisal of our recent article, in which we evaluated the impact of age on the diagnostic performance of high-sensitivity cardiac troponin for myocardial infarction. 1 Chen et al highlight the importance of considering renal function when interpreting elevated cardiac troponin concentrations in older people. Two of every 5 patients with suspected myocardial infarction and renal impairment have cardiac troponin concentrations above the 99th centile upper reference limit.
…”
mentioning
confidence: 99%
See 1 more Smart Citation